2016
DOI: 10.17795/nmsjournal35594
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Problem-Focused Coping Strategies on the Burden on Caregivers of Hemodialysis Patients

Abstract: BackgroundStudies have shown that family caregivers of hemodialysis patients experience high levels of burden. However, these caregivers are often neglected, and no studies are available on the effectiveness of coping strategies on the burden of care among these caregivers.ObjectivesThis study aimed to examine the effectiveness of problem-focused coping strategies (communication skills, anger management, and deep breathing) on the burden on caregivers of hemodialysis patients.Patients and MethodsA randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 29 publications
3
62
0
1
Order By: Relevance
“…32,33 It has been suggested that a problem-focused strategy is appropriate for managing problems. 4 In this regard, Abbasi et al showed that using problem-focused coping significantly reduced the perceived caregiver burden. Caregivers who used problem- focused strategies also had less time-dependent care burden and less physical care stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32,33 It has been suggested that a problem-focused strategy is appropriate for managing problems. 4 In this regard, Abbasi et al showed that using problem-focused coping significantly reduced the perceived caregiver burden. Caregivers who used problem- focused strategies also had less time-dependent care burden and less physical care stress.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, Ghane et al reported that the use of problem-focused coping reduced the care burden of hemodialysis patients' caregivers. 4 Such factors as sociocultural characteristics of caregivers and level of perceived care burden by caregivers are associated with the type of selected coping strategy. 3,9 These factors can account for the discrepancy among the results of different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, actions that may create a risk to caregivers safety increases subjective burden such as hostility or aggression, demolition of possessions and substance abuse [11]. It is subjective burden that describes the psychological reactions such as unhappiness, nervousness, the stress of coping with disturbing behaviours and the frustration caused by changing relationships [12,13]. Certainly, caring on its own comes with a whole lot of challenges and occasionally distress which affects caregiving and also negatively impacts the overall physical health of caregivers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the caring role of caregivers can increase their sense of kindness and love and provide them with benefits such as greater intimacy in family relationships, meaning in life, respect for themselves and others, and self-satisfaction, studies show that caring responsibility puts a great amount of pressure on caregivers' physical and mental health (3,8). The day-to-day support that family members provide for their spouse, parents, and partner who is suffering from the disease has significant physical, psychological, and economic costs and consequences such as inability to solve problems, economic stresses, changes in the roles of the family, threats, changes in life expectancy and feelings of loneliness which include fear of being abandoned.…”
Section: Introductionmentioning
confidence: 99%